Determinants of the expansion of the Brazilian sugar-energy industry in the early 21st century - Henrique Santos (Geografares, 2023)
This article aims to comprehensively examine the primary market factors that propelled the expansion of the sugar-energy industry in Brazil during the first two decades of the 21st century. This period witnessed a significant surge in the number of sugar-energy industry plants and the expansion of cultivated areas, particularly in the Center-South region of Brazil. The escalating national and international demand for sugar and ethanol, driven partially by the appreciation of these commodities and the pivotal role of ethanol in mitigating Greenhouse Gas (GHG) emissions that contribute to climate change, has spurred significant investments from prominent domestic and multinational corporations in the sector. These investments have led to the modernization of productive and logistical operations, as well as the geographical expansion of sugarcane cultivation and processing, culminating in an upswing in the exportation of key industrial derivatives.
Keywords: sugarcane industry; Brazil; agriculture